PENGGUNAAN KAWAT PVF DAN CWUNTUK LILITAN TRANSFORMATOR PRIMER DAN SEKUNDER APLIKASI PT.MORAWA ELEKTRIK - Muhammad Adam (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
PWF wire and wire CW is used copper wire as the primary and secondary performance windings.Conductivity perfect is 100% and the price is affordable when if use gold or platinum.